di STRATEGI KOMUNIKASI OBJEK WISATA SITU GUNUNG SUSPENSIONS BRIDGE DI MASA NEW NORMAL - Fakhriyah Nur Hasna; Nurfalah Annisa; Safana Aura Nadiva; Brendha Qaulani Tsakila (UHN IGB Sugriwa Denpasar, 2022)
Since the COVID-19 pandemic, the tourism sector in Sukabumi Regency, especially the Situ Gunung Suspension Bridge tourist attraction, has experienced a decline in income due to the government's policy regarding Large-Scale Social Restrictions (PSBB) which requires the public to limit social activities to reduce the increase in the number of COVID-19 patients. The role of the tourism sector is one of the major influences in increasing the economy in a region. Therefore, this study aims to examine how the Situ Gunung Suspension Bridge tourist attraction strategy in the new normal era, of course, there are new policies that must be adjusted by tourists. This analysis was conducted using the descriptive-qualitative method. The results of this analysis were obtained from various sources, namely mass media, online media, and also literature studies. from the analysis obtained, the Situ Gunung Suspension Bridge tourist attraction carries out a strategy by utilizing digital media as a tool to convey information and promotions as well as making new innovations in tourism objects to attract tourists to visit Situ Gunung Suspension Bridge.